Nominative objects in Korean - Park Chongwon; Kim Jong-Bok (Linguistics)
This article addresses the hitherto neglected topic of the Korean Nominative Object Construction (NOC) within the Cognitive Grammar (CG) framework. In the NOC, schematically illustrated as [N-NOM N-NOM PSYCH-PRED], the second NP behaves like a direct object. While the construction has puzzled many researchers in different languages, and a sizable amount of research exists, relatively little attention has been paid to Korean. It is worth noting that the findings made in the extant generative-linguistic research – including the research on Japanese, which exhibits significant typological similarities to Korean – are not sufficient to account for the Korean data. After identifying the properties of the Korean NOC, we demonstrate that the NOC merely reflects how the experiencer conceptualizes the stimulus that exists in a certain domain of mental experience within her mind. This internal representation of the stimulus is marked nominative by being the sole participant in the relationship profiled by the psychological verb at the lower level of organization. At the higher level of organization, the first nominal is the primary participant as an experiencer, thereby receiving nominative case as well. Our analysis is extended to the desiderative construction, which exhibits similar patterns to the PSYCH-PRED NOC but allows alternation of case in the second nominal between nominative and accusative marking. The case alternation is motivated by two different types of construals of the same conceptual base. The nominative marking arises when the embedded transitive relationship is backgrounded, whereas the accusative marking becomes available when the profile is given to the transitive relationship. We demonstrate that the source of the case alternation lies in the profile, rejecting the dichotomous division of the construction based on its mono- or bi-clausal properties.